Analisis pengelolaan keuangan pada bisnis online Indah Widia Multibeauty di Kabupaten Tulungagung - Yulia Nur Anggraeni (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Financial analysis is an effort made to evaluate business continuity. The rise of online business entrepreneurs at this time, in the midst of the COVID-19 pandemic situation with restrictions on social activities, makes online business an alternative that can be considered. This research is focused on the financial management side of online business. No exception in managing finances in a business. With an online business, Ms. Indah Widia Multibeauty as an object of research with Islamic financial management applied in online business. The focus of the research in this journal is (1) How is the financial management of the beautiful online business of Widia Multibeauty? (2) Is the financial management of the Indah Widia Multibeauty business in accordance with the principles of Islamic accounting financial management?. This research method uses a qualitative research approach with the type of case study research. The results of this study indicate that these micro-enterprises or online business actors in financial management at Indah Widia's business still use simple financial management. These micro business actors or online business actors have implemented Islamic financial management because it is in accordance with the principles of Islamic buying and selling. Keywords: Online Business, Financial Management, Business Management, Micro Business Actors, Product Cost